2009
DOI: 10.1590/s1413-70542009000600025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentrate: voluminous ratio on the performance of Santa Inês lambs

Abstract: The experiment was carried out in the sheep division of Universidade Federal de Lavras, aiming to evaluate the effect of different concentrate : voluminous ratio on the performance of Santa Inês lamb after wean. 40 lambs, male uncastrated, were used and fed with four different diets: diet A (100% concentrate), diet B (75:25 concentrate : voluminous) , diet C (50:50 concentrate : voluminous) , diet D (25:75 concentrate : voluminous). The experimental diets were isoproteic, differing only on its levels of concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…These values are higher than those that were found in the present study, likely because those authors used much higher CP levels. Lower ADG values were observed by Oliveira et al (2009) when evaluating the effects of concentrate levels in diets containing 16.3% CP on the performance of Santa Inês lambs slaughtered at 35 kg. The authors found ADGs in lambs that were fed diets with 75% and 100% concentrate of 160 and 146 g/day, respectively.…”
Section: Animal Performance and Carcass Traitsmentioning
confidence: 85%
See 2 more Smart Citations
“…These values are higher than those that were found in the present study, likely because those authors used much higher CP levels. Lower ADG values were observed by Oliveira et al (2009) when evaluating the effects of concentrate levels in diets containing 16.3% CP on the performance of Santa Inês lambs slaughtered at 35 kg. The authors found ADGs in lambs that were fed diets with 75% and 100% concentrate of 160 and 146 g/day, respectively.…”
Section: Animal Performance and Carcass Traitsmentioning
confidence: 85%
“…Oliveira et al (2009) found a FC of 5.03 and 5.10 for diets containing 100% and 75% concentrate, respectively. Moreno et al (2010) found no differences in FC in lambs that were fed diets with forage: concentrate ratios of 60:40 and 40:60, while also observing an average of 3 kg DM/kg of body weight gain.…”
Section: Animal Performance and Carcass Traitsmentioning
confidence: 92%
See 1 more Smart Citation
“…Sheep breeding is one of the main economic activities of the northeast, mainly for meat production, which satisfies much of the demand for animal protein for the local population. However, the production system in this region is characterized as extensive, showing low stocking rate of native pastures, low meat and low reproductive efficiency, resulting in a low economic performance to farmers The growing demand for sheep meat, registered over the last years, propelled the increase in the lamb production for slaughter, creating a necessity of improvement in the exploration techniques (OLIVEIRA et al, 2009). Quality and quantity of feed are the major factors in increasing ruminant productivity under tropical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…formulation diets (Taher, et al, 1987). Oliveira, et al, (2009) and Ebrahimi, et al, (2007) stated that increasing the level of protein and energy concentrations in ruminants' diet will improve the feed conversion ratio and reduce the period to reach a slaughter weight. In this respect, Qasim et al, (1993) added non-protein nitrogen sources to barley to improve the efficiency of animal utilization.…”
mentioning
confidence: 99%